JUNIOR HIGH SCHOOLS TEACHERS’ PERCEPTION ON THE IMPLEMENTATION OF UJI KOMPETENSI GURU TO ASSESS PROFESSIONAL DEVELOPMENT - Nadia Aprilia Listyantari (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2020)
This research explores teachers’ perception on the implementation of UKG to assess professional development. UKG is one of the government policies that must be followed by teachers who are still actively teaching. The implementation of UKG is expected to map teachers’ competence whose results will be followed up as a reference in the development of teachers’ competency and professionalism so that they can reach the expected result based on the Standar Nasional Pendidikan or National Education Standards (SNP). Survey research is conducted since the researcher needs a method that is able to make the result of this study represents the population of junior high school teachers. Teachers’ perception are divided into three main parts which each of them focuses on teachers’ understanding before taking UKG, teachers’ views about UKG after taking the test, and teachers’ action for the upcoming UKG.